ANALISIS KERJA GURU SMP NEGERI SE- KOTA MAKASSAR - Syarifuddin Syarifuddin (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2019)
As the capital of the province, education in the Makassar supposed to be better than other cities in the province of South Sulawesi. In fact, the quality of education is still far from expectation. So was the result of the theacher’s competence test. Likewise, teacher competency test result, data on the Department of Education in Makassar to participants of UKG in Makassar is the average value of fewer than 50. In fact, there are teachers who receive 30 from 100 questions in the exam. The condition is not in line with the role of the teacher that is crucial in improving the quality of education. Therefore, it is very important to improve the performance of teachers in all junior high school in Makassar in order to improve the quality of education with the problems of this research consist of (i) how is the performance of the teachers on all State secondary schools in Makassar? This research aims at (i) finding out the teachers’ performance on all State secondary schools in Makassar; The results show that (i) the teachers’ performance on all State secondary schools in Makassar are on the good category. Sebagai Ibukota Propinsi seharusnya Pendidikan di Kota Makassar lebih baik jika disbanding kabupaten/kota lain di Propinsi Sulawesi Selatan tetapi kenyataannya kualitas pendidikan masihjauh dari harapan. Demikian juga hasil Uji Kompetensi Guru, data Dinas PendidikanKota Makassar untuk peserta UKG di Kota Makassar, yakni rata-rata nilai di bawah lima puluh. Bahkan,ada guru yang mendapatkan nilai tiga puluh dari seratus soal dalam naskah ujian.Kondisi tersebut tidak sejalan dengan peran guru yang sangat penting dalam peningkatan kualitas pendidikan.sangat penting meningkatkan kinerja guru se-Kota Makassar dalam upaya meningkatkan kualitas pendidikan. Oleh karena itu rumusan masalah dalam penelitian ini adalah (i) Bagaimanakah kinerja guru-guru SMP Negeri se-Kota Makassar? Tujuan penelitian ini adalah (i) Untuk mengetahui kinerja guru-guru SMP Negeri se-Kota Makassar Hasil penelitian menunjukkan (i) kinerja guru SMP Negeri se-Kota Makassar berkategori baik.